Current opinions in Kawasaki disease - (:unkn) unknown (My University, 1996)
One of the common childhood vasculitis, Kawasaki Disease, (KD) is characterized by persistent fever, bilateral conjunctival injection, oropharyngeal mucous membrane changes, erythema and/or edema of hands, polymorphous rash, and cervical lymphadenopathy. Recovery is generally complete in patients who do not have detectable coronary vasculitis. Aspirin is the mainstay of treatment and is used to prevent thrombus formation and ischemic heart disease. Intravenous gamma globulin reduces the fever and systemic manifestations of the disease and decreases the incidence of coronary artery aneurysms.